Financing energy transition in COVID-19 for energy efficiency: Does mitigation of energy price risk that essential? - Shao, Ming; Wang, Lulu (Frontiers in Environmental Science, 2022)
The aim of the study is to test the nexus between energy prices risk and energy efficiency for energy transition to recommend the implication for the period of COVID-19 crises. This study uses short-term daily data of G-20 countries for COVID-19 crises was taken to better estimate the study findings. To estimate the results Data Envelopment Analysis (DEA) estimation method was applied for empirical inference. The findings revealed that the COVID-19 crises have the biggest negative influence with 47.1% on oil prices which raised energy prices risk at large. The aforementioned results hold even after substituting the magnitude of extreme list of variables, re-estimating the equations with energy efficiency. Such risk has further halted energy efficiency with 33.69% in G-20 countries during COVID-19 which is one of the largest dent of the mankind history. Our results also inferred that the relationship of energy prices risk with energy efficiency remained significant but negative with energy transition. Extending to it, the post-COVID-19, the danger of energy stock price crashes is expected to diminish dramatically. The study suggest that the corporations must participate in greater corporate social responsibility (CSR) activities have lower post-COVID-19 energy price collapse risk. Finally, we demonstrate that post-COVID-19, the impact of COVID-19 on energy price collapse risk.